SINKRONISASI ANTARA PERENCANAAN NAGARI DENGAN PERENCANAAN PEMBANGUNAN DAERAH DI KABUPATEN SOLOK - Asdi Agustar; Ira Wahyuni Syarfi; Elma Wati (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2021)
This study aims to determine the synchronization of planning at the village level with development planning at the district level in Solok Regency and to determine the problem of synchronizing planning at the village level with development planning at the district level in Solok Regency. This study analyzes the planning documents at the village level, namely the Nagari RPJM 2013-2019 and the 2017-2019 Nagari RKP with the Solok Regency planning documents, namely the Solok Regency RPJMD 2016-2021 and the Solok Regency RKPD 2017-2019 using the case study method on 4 Nagari cases based on the Village Development Index (IDM) in 2019 are: (1) Nagari Talang (advanced nagari), (2) Nagari Aie Batumbuk (developing nagari), (3) Nagari Labuah Panjang (lagging nagari), and (4) Nagari Sarik Alahan Tigo (a very lagging village) with a combination of quantitative (content analysis and assertion analysis) and qualitative approaches. The aspects analyzed in this study are the vision, mission, goals, and objectives of the RPJM as well as the policy direction in the RKP. The results of the analysis will be grouped into four levels of Krippendorff's relationship, namely strong, medium, weak, and unrelated. The results of this study are: (1) a vision related to the vision of Solok Regency; (2) The mission is strongly related to the mission of Solok Regency; (3) objectives are weakly related to the objectives of Kabupaten Solok; (4) The target is weakly related to the target of Solok Regency; and (5) the Nagari RKP is strongly related to the Solok Regency RKPD. Problems in this synchronization can be seen in the weak human resources of the village and the absence of monitoring and evaluation of the planning documents. The study recommends the formation of an independent village team that works in coordination with the Solok Regency government, as well as the district's assistance to the village in the preparation of village planning documents. Key words: Synchronization; Planning; Development; RPJM; and RKP